Improving development of competitive economy on innovation and investment basis - Шталь, Тетяна Валеріївна; Дядін, Андрій Сергійович (Technology audit and production reserves, 2015)
The influence of innovation and investment factor for improving the competitiveness of the state’s economy is investigated. The essence and features of the innovation and investment development are considered. There are determined the conditions by which the level of competitiveness of the national economy will grow. The impact factors on the investment climate of the country are determined. The ways to overcome them are proposed. The influence of individual factors on the viability of innovation project is investigated. Practice of economic feasibility of management solutions require new approaches for analyzing and forecasting processes in order to assess the quality of management of competitiveness on the basis of the rating analysis of innovation and investment processes, and determine the relevance of the study, the results of which can be the basis for developing an effective innovation and investment policies. As a result of our investigation, it is concluded that the orientation of Ukrainian economy on the export of raw materials leads to significant reduction in competitiveness and innovation, and foreign exchange and operational risks, freedom of movement of capital and profits, availability of production of market infrastructure are the main factors influencing the competitiveness of the economy through innovation and investment development. On the basis of our proposed methodology for assessing the factors influencing the competitiveness through innovation and investment, it is possible to effectively prevent the existing risks and threats to the underinvestment of existing competitive advantages.